The Challenges of Cultural Criminology - Bilinović, Ana; Kojić, Milena (Zbornik Instituta za kriminološka i sociološka istraživanja, 2015)
Cultural criminology is a specific approach to the study of crime and its control in the context of culture and as a product of culture. The main field of research in cultural criminology is the analysis of the interinfluence between criminal subculture, criminal situation and media constructions of crime. This paper presents the theoretical and methodological foundations of cultural criminology, with a special focus on ethnographic research, subcultural ethnography, contextual picture of crime and textual analysis in the field of cultural criminology. Special attention is paid to the contemporary research fields of cultural criminology: "crime as culture", "culture as a crime", the media construction of crime (controle) and politics of cultural criminology, with a focus on the specific issues that characterise this contemporary field of interest among cultural criminologists.